(3GdJdbjf aj abg GdeGdcjIs - (3CHh eMeO YHO GdhgGH Hf Ydj Hf fUQ GdHZOGOj GdbQGaj GdeGdcjs ((3RjGf Hf YeQ Hf eaJGM Hf CHj Yajai s)
(3ChdgG (B:s
(3bGd GdbGVi GdLdjd CHh eMeO fMeO Gddg hfTcQg hfSJYjfg cJGH GdWgGQI s
(3BNQgG (B:s
(3hbO CJjfG ai gPG GdeNJUQ Ydi eG fSCd Gddg YR hLd GdfaY dfG Hg hdce heYGTQ GdENhGf ajg hGdSdGe Ydjce hQMeg Gddg JYGdi hHQcGJg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(405 / 40) s
Keywords: (3Gdabg GdeGdcjs